Silent Reading Training Improves Reading Speed and Reading Comprehension - Herdiana; Munir, Sirojul (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
The speed reading and reading comprehension abilities of junior high school students are still far from ideal criteria. There are still many students who do not understand reading quickly and well. The aim of this study was to examine the effect of fast and silent reading skills training on students' reading speed and achievement at an early age. This research also seeks to explore the effectiveness of training interventions and their potential for students based on gender. The research method used in this research is quasi-experimental. The participants involved in this research were 350 junior high school students in grades 1-3. The experimental group received speed reading skills training 15 times using Indonesian language books. The control group used the regular curriculum. The data analysis used is correlation analysis between variables based on sample data, data range, skewness and kurtosis. In addition, ANCOVA analysis was carried out to determine the impact of the intervention on fast reading skills silently through pre- and post-intervention score analysis. The results showed that students in the experimental group showed a higher reading speed than students in the control group. Students who received intervention showed a better level of reading effectiveness in the posttest phase compared to the reading ability of students in the control group. In terms of gender, male students show better reading speed than female students. However, in terms of reading comprehension level, male and female students showed similar improvements in the posttest phase.